2006
DOI: 10.1007/s00442-006-0621-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas

Abstract: Global climate models predict that in the next century precipitation in desert regions of the USA will increase, which is anticipated to affect biosphere/atmosphere exchanges of both CO(2) and H(2)O. In a sotol grassland ecosystem in the Chihuahuan Desert at Big Bend National Park, we measured the response of leaf-level fluxes of CO(2) and H(2)O 1 day before and up to 7 days after three supplemental precipitation pulses in the summer (June, July, and August 2004). In addition, the responses of leaf, soil, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 53 publications
5
60
1
Order By: Relevance
“…For example, measuring the responses of leaf, soil, and ecosystem to a 25% increase in precipitation (via manipulation of precipitation) during the summer in the Chihuahuan Desert, researchers found that ecosystem C uptake and soil CO 2 efflux increased following individual watering events despite that measured stomatal conductance remained the same (Patrick et al 2007). However, at the seasonal scale, water additions resulted in an increase in sequestration of atmospheric C and a decrease in soil CO 2 efflux (Patrick et al 2007).…”
Section: Combined Microbial and Vegetation Responses In The Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, measuring the responses of leaf, soil, and ecosystem to a 25% increase in precipitation (via manipulation of precipitation) during the summer in the Chihuahuan Desert, researchers found that ecosystem C uptake and soil CO 2 efflux increased following individual watering events despite that measured stomatal conductance remained the same (Patrick et al 2007). However, at the seasonal scale, water additions resulted in an increase in sequestration of atmospheric C and a decrease in soil CO 2 efflux (Patrick et al 2007).…”
Section: Combined Microbial and Vegetation Responses In The Soilmentioning
confidence: 99%
“…For example, measuring the responses of leaf, soil, and ecosystem to a 25% increase in precipitation (via manipulation of precipitation) during the summer in the Chihuahuan Desert, researchers found that ecosystem C uptake and soil CO 2 efflux increased following individual watering events despite that measured stomatal conductance remained the same (Patrick et al 2007). However, at the seasonal scale, water additions resulted in an increase in sequestration of atmospheric C and a decrease in soil CO 2 efflux (Patrick et al 2007). While soil CO 2 efflux increased immediately after precipitation and for a few hours (;18 h), once the ecosystem entered an interpulse period and soil moisture decreased, rates of soil CO 2 efflux from wetted plots declined faster than in plots without water addition (Patrick et al 2007).…”
Section: Combined Microbial and Vegetation Responses In The Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diel tent-based measurements of NEE in a Chihuahuan desert grassland revealed midday depression of ecosystem CO 2 assimilation with implications for net ecosystem productivity (Patrick et al 2007). Furthermore, daytime measurements of ecosystem respiration may not be representative of nighttime ecosystem respiration, particularly in regards to the contribution of autotrophic respiration (Tang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, by combining evaporation from soil and canopy surfaces with transpiration from stomata, evapotranspiration (ET) is critical in understanding the role of ecosystems in linking the movement of water between the land surface and the atmosphere. Used in a variety of experimental settings, chamber-based measurements have demonstrated the effects of seasonal rainfall (Harpole et al, 2007;Patrick et al, 2007), rainfall timing (Potts et al, 2006) and fire (Prater and DeLucia, 2006) on CO 2 exchange and ET.…”
Section: Introductionmentioning
confidence: 99%